The relationship between corporate responsibility and the performance of the company - Frolova, Yuliya; Sakulyeva, Tatyana; Hammam, Kareem (Opción, 2020)
The purpose of the research is to study and deepen the theoretical provisions regarding the relationship between corporate responsibility and the performance of organizations via a set of scientific methods of cognition. The results obtained demonstrate certain differences in the impact of corporate responsibility on the activities of enterprises in the context of different countries of the world. The practical relevance of the research conclusions and recommendations lies in the possibility of their practical application at the level of the state and individual business entities, which will allow creating social and economic value for all interested parties.